2018
DOI: 10.1037/bul0000115
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of two modes of learning and the description-experience gap.

Abstract: People can learn about the probabilistic consequences of their actions in two ways: One is by consulting descriptions of an action's consequences and probabilities (e.g., reading up on a medication's side effects). The other is by personally experiencing the probabilistic consequences of an action (e.g., beta testing software). In principle, people taking each route can reach analogous states of knowledge and consequently make analogous decisions. In the last dozen years, however, research has demonstrated sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
368
9

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 252 publications
(392 citation statements)
references
References 159 publications
15
368
9
Order By: Relevance
“…Our experience‐based probability format is inspired by the decision from experience method (Ashby, ; Barron & Erev, ; Hertwig, Barron, Weber, & Erev, ; Traczyk et al, ; Wulff, Mergenthaler‐Canseco, & Hertwig, ) in which people can freely explore the environment and learn its properties (e.g., probabilities and outcomes). 1 However, this line of research focused on choices and decision‐making processes rather than communication of probability.…”
mentioning
confidence: 99%
“…Our experience‐based probability format is inspired by the decision from experience method (Ashby, ; Barron & Erev, ; Hertwig, Barron, Weber, & Erev, ; Traczyk et al, ; Wulff, Mergenthaler‐Canseco, & Hertwig, ) in which people can freely explore the environment and learn its properties (e.g., probabilities and outcomes). 1 However, this line of research focused on choices and decision‐making processes rather than communication of probability.…”
mentioning
confidence: 99%
“…For example, when consumers choose between investments or grocers, they need to trade off investment returns (or discount magnitude) with investment risks (or discount frequency), or when they choose between medical treatments, they need to trade off the positive (partial or full treatment) and negative outcomes (side effects) of each treatment with the likelihood of these events (Saporta‐Sorozon, Danziger, & Sloman, ). Second, much of the literature examining differences between description‐based and experience‐based choice examined choice between gambles (Barron & Erev, ; Hertwig, ; Hertwig et al, ; Wulff, Mergenthaler Canseco, & Hertwig, in press).…”
mentioning
confidence: 99%
“…Third, underweighting is moderated by the structure of the decision problems. Wulff et al () found that underweighting is greater when the rare outcome is extremely rare, when one option is risky (has more than one possible outcome) while the other is safe (has only one outcome), and when the prospects contain losses.…”
Section: Research On Sampling Strategies In Decisions From Experiencementioning
confidence: 99%
“…We now focus on the second question regarding optional stopping. Optional stopping refers to situations in which participants decide how much data to collect in a sequential manner, which can be influenced by many factors (Fried & Peterson, ; Gonzalez & Dutt, , ; Markant, Pleskac, Diederich, Pachur, & Hertwig, ; Wulff et al, ).…”
Section: The Relation Between Optional Stopping and Final Decisionsmentioning
confidence: 99%